Toward a More Reflexive and Deliberative Public Affairs: A Critical Reimagining of Doctoral Training. (3rd September 2022) - Scott, Charity P.; Glickman, Alannah R.; DiTommaso, Adrienne
Abstract: Doctoral students occupy a unique space in academia: as future scholars and instructors, they are both trainees and trainers, positioned to reproduce research and teaching practices as well as to disrupt and improve them. The role of the state in the social, political, and economic crises of 2020, including the COVID-19 pandemic and continuous, racialized police violence, has highlighted the need to critically interrogate public affairs' (PA) norms and values. The "New Four E's" (empathy, engagement, ethics, and equity) suggest a reorientation of the field's norms and values towards social justice. As part of this field-level shift towards more just public affairs, this paper offers a reimagining of PA doctoral training by institutionalizing the socioemotional processes of reflexivity and deliberation in three key areas of doctoral training: core coursework, pedagogical training, and professional development. The argument outlined in this paper draws on literature from the fields of public administration, education, pedagogical philosophy, psychology, management, and sociology to stimulate dialogue and action among PA scholars and practitioners with the ultimate goal of embedding the New Four E's as core field values.